STRATEGI PENGGUNAAN TEKNOLOGI EDUKASI DALAM MENINGKATKAN KEMAMPUAN BAHASA DAN KOGNITIF ANAK USIA DINI DI TK NEGERI PEMBINA 5 - Nur Anisyah; Siti Marwah; Arisnawati; Septri Nurjanah; Rani Febriyana; Diah Siti Aisyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Advances in digital technology are increasingly providing new opportunities for early childhood learnin8g. This study aims to analyze strategies for using educational technology to improve the language and cognitive skills of 5-6-year-old children at Pembina 5 State Kindergarten. The research method used a descriptive qualitative approach through observation, interviews, and documentation. The study subjects consisted of 29 children from Group B and two classroom teachers. The results showed that the use of educational technology, such as interactive videos, educational game applications, and audiovisual media, has been shown to improve children's language comprehension, vocabulary, listening skills, logical thinking, problem-solving, and memory. The strategies implemented included gradual use of technological media, teacher support, integration with thematic curricula, and observation-based evaluation of learning outcomes. Thus, educational technology can be an effective and enjoyable learning tool to support the language and cognitive development of early childhood.